Problems with IPv6 Implementation - Vladimír Nulíček (Acta Informatica Pragensia, 2018)
The aim of the article is to describe the current status of IPv6 implementation in the Czech Republic and in the world, including the comparison of the different IPv4 and IPv6 transition mechanisms and the outlook for the future. The article is based on extensive research of current sources related to this issue, available on the Internet. It also describes the major security risks associated with the new IP protocol version. Attention is also paid to the economic evaluation of the implementation of IPv6. The article should help those interested in moving to IPv6 to better focus on this complex issue.